PENGEMBANGAN MEDIA PEMBELAJARAN MIA (MULTIMEDIA INTERACTIVE AND AUTOMATIC) BERBASIS HYPERCONTENT MATA PELAJARAN EKONOMI DI MADRASAH ALIYAH AL AMIRIYYAH PONDOK PESANTREN BLOKAGUNG BANYUWANGI - Irnawati; Nurmida Catherina Sitompul; Nunung Nurjati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop hypercontent-based Multimedia Interactive and Automatic (MIA) Learning Media for Economics subjects at Madrasah Aliyah Al Amiriyyah, Blokagung Islamic Boarding School, Banyuwangi. MIA is designed to utilize communication and information technology, with the aim of presenting interactive and automatic materials to increase student engagement in learning. With hypercontent-based MIA, it is expected that students can access materials in an interesting and efficient manner and improve their understanding of the material being taught. The research model used is Research and Development (R&D) with the Dick and Carey approach, which involves ten development steps. These steps include analysis of objectives, context, and students, material development and evaluation, and field trials after the product is completed. The assessment was carried out by material, media, and learning design experts, as well as small group and field trials with learning outcome tests. The results of the expert assessment showed that this product was interesting, fun, and interactive, with a score of 92% for learning design, 96% for material, and 90% for media. The results of the study indicate that hypercontent-based MIA is effective in increasing student motivation, engagement, and understanding of economic concepts. The analysis showed a significant difference between classes using MIA and those without, with higher average test scores in classes using the product. In conclusion, hypercontent-based MIA is effective and worthy of further development to support independent and interactive learning, and is relevant for improving the quality of education in Islamic boarding schools and other educational institutions.